Friend or foe? Foreign donors’ role in the formation of civil society in Ukraine - Shevtsova, Maryna (Socio.hu Társadalomtudományi Szemle, 2017)
For a long time, civil society in independent Ukraine lacked visibility and seemed passive and underdeveloped. Yet lately foreign observers have defined civil society in Ukraine as the richest in the former Soviet Union in terms of the number and variety of organizations. In the aftermath of the Revolution of Dignity, as the state institutions are unable to perform their basic functions, civil society organizations (CSOs) have been compelled to take over some of their duties, getting involved into multiple spheres of public life, such as volunteering in the army, crowd–funding for internally displaced people and military needs. They are particularly strong in advocacy for reforms and acting as watchdogs of institutional change. However, while having proven its resilience in crisis, civil society in Ukraine still shows low sustainability and a high level of dependency on foreign donors. Having acknowledged the positive role of foreign donors in the development of national civil society, the present article goes beyond this one–sided evaluation and answers the following questions: How do foreign donors influence Ukrainian CSOs working with civic participation and human rights advocacy? What are the main obstacles the CSOs face on the way to full independence and sustainability in post–Euromaidan Ukraine in the years 2014–2017? Drawing on the empirical data collected through the analysis of major national media sources and social media, participant observation, and interviews with civil society actors, policy–makers and foreign donors’ representatives, this article argues that the role of foreign donors may be more complex than the way it used to be portrayed, as it should be assessed in the context of domestic social and political dynamics. The failure to do so may lead to unintended consequences and render previous achievements null. Keywords: civil society, Ukraine, foreign aid, civil society organizations